The assessment of shoulder instability. The development and validation of a questionnaire. - Dawson, J; Fitzpatrick, R; Carr, A (1999)
We have developed a 12-item questionnaire for completion by patients presenting with shoulder instability. A prospective study of 92 patients was undertaken involving two assessments, approximately six months apart, performed in an outpatient department. Each patient completed the new questionnaire and the SF36 form. An orthopaedic surgeon completed the Constant shoulder score and the Rowe assessment. The new questionnaire and the Rowe clinical score each achieved a large standardised effect size (> or = 0.8) and compared favourably with relevant items on the SF36. By contrast, the Constant score barely registered any effect, confirming that it may be relatively insensitive to changes in clinical status for this particular condition. The questionnaire provides a measurement of outcome for shoulder instability which is short, practical, reliable, valid and sensitive to changes of clinical importance.